Sub-populations of haemocytes in the adult and developing marine mussel, Mytilus edulis , identified by use of monoclonal antibodies - Dyrynda, E. A.; Pipe, R. K.; Ratcliffe, N. A. (Cell and tissue research, 1997)
Monoclonal antibodies specific for haemocyte sub-populations in the mussel, Mytilus edulis, were raised by use of separated basophilic and eosinophilic cell types as antigens. The antibodies could be broadly divided into 3 groups, reactive with sub-populations of (1) basophilic granular haemocytes, (2) basophilic granular and hyaline cells and (3) eosinophilic granular cells. Non-selective antibodies staining all haemocytes were also generated. The antibodies bound to epitopes of differing molecular masses and, at the ultrastructural level, reacted principally with the granules of the haemocyte sub-populations. The antibodies were used to investigate haemocyte function and ontogeny and to test reactivity with haemocytes from mussels subject to varying degrees of pollution stress. Five antibodies showed reactivity with cells from the trochophore and veliger larvae of M. edulis, indicating that epitopes on adult mussel hae-mocytes are also present at much earlier stages in the life history. Reactivity with the larval stages was most prevalent with non-selective antibodies and those selective for basophilic haemocytes. When mussels from different sites were examined, both immunocytochemistry and ELISA showed reduced expression of a 140 kDa epitope in the haemocytes of mussels subject to greater contaminant loads. These results show that the monoclonal antibodies of the present study are valuable both in tracing immune-cell development and in detecting molecular changes under conditions of stress.